THE IMPACT OF GOVERNMENT SPENDING IN EDUCATION AND HEALTH ON ECONOMIC GROWTH IN INDONESIA 2014-2023 - Erwin Iswahyudi; Hendry Cahyono (Publikasi Inspirasi Indonesia, 2025)
This study aims to analyze the influence of government spending in education and health on economic growth in Indonesia in the period 2014–2023. This research is motivated by the Indonesian government's commitment to achieve the Sustainable Development Goals (SDGs) through Asta Cita towards Indonesia Emas 2045, one of which emphasizes the importance of human resource development through education and health. The method used is a descriptive quantitative approach with panel data regression analysis utilizing secondary data from 34 provinces in Indonesia. The results of the study indicate that partially, government spending in education has a negative but insignificant effect on economic growth, while government spending in health has no significant effect. Simultaneously, both variables also have no significant effect on Indonesia's economic growth. This study recommends that the government optimize budget allocation by increasing capital expenditure and goods/services expenditure that support the quality of education, as well as strengthening promotive and preventive programs in the health sector to improve the quality of human resources and sustainable economic growth.